Implementation of a Deep Learning Approach in Teaching Fiction Reading for Phase D Students in Junior High School - Jilia Anggun Ramadani; Sophia Rahmawati; Lusia Oktri Wini (Asosiasi Dosen Muda Indonesia, 2026)
This study implements a deep learning approach in the classroom. The goal is to determine how the deep learning approach is applied to the teaching and learning process and how it can help students easily understand the material being studied in depth. This study uses a descriptive qualitative research method, so the results are presented in detail and based on classroom findings and a case study. The data consists of primary and secondary data. Data collection techniques include observation, interviews, and documentation. Data analysis involves describing the data obtained. The results show that students participate more actively in learning using the deep learning approach.